Between Performance and Action ? about a Certain Variant of Research that Uses Art - Pryszmont-Ciesielska, Martyna (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The aim of the article is to present the model of research that uses art in the original project of ?Socially excluded mothers?. The goals of the research are oriented, amongst others, for learning about the experiences of socially excluded mothers; prompting self-reflection of the researched women on their maternity experiences and making the research participants and recipients sensitive and building their critical reflection connected with the experiences of the researched women. The suggested model of research through art takes on a form of a participatory, critical and socially engaged research practice. In this text there have been discussed subsequent stages of the applied model. What is specific here is the involvement of art elements in the investigation proccess. On the basis of the conducted research there will be prepared scenarios for the actresses invited to the project, whose task will be to enact the researched women. These scenes will be filmed and then made public during the performance.